Optimization of Time, Temperature, and pH for the Extraction of Anthocyanin from Buni (Antidesma bunius) Fruit - William Juhadi; Abdullah Muzi Marpaung (Food Science and Technology Journal (Foodscitech), 2021)
The Box-Behnken design to find the optimum condition for anthocyanin extraction of Buni (Antidesma bunius) fruit powder was applied. Color intensity (CI), total monomeric anthocyanin (TMA), total phenolic content (PC), and antioxidant activity (AA) were the parameters selected to express optimality resulted from the extraction process. The three studied factors were temperature (30-90oC), time (30-90 minutes), and pH of solvent (1-3). The extraction was conducted in a water bath shaker under no light by HCl-acidified water as a solvent with a 1:25 (w/v) powder to solvent ratio. The quadratic model described the effect of factors on CI, TMA, and AA of buni fruit extract, while the linear model suitable for the total phenolic content. All factors influenced the CI and TMA, but time was insignificant for PC and antioxidant activity (p < 0.05). The optimum parameter for extraction was at 68oC for 30 minutes with pH 1 solvent. The 95% confidence interval of CI, TMA, PC, and AA were 40.29 ± 0.91, 555.17 ± 13.34 mg/l, 1084.4 66.845 ± 66.85 mg GAE/l, and 45.00 ± 2.56 % inhibition, respectively. The color and anthocyanin stability test showed that the extract was almost colorless at pH 5-6, but the anthocyanin was relatively stable with half-life 28 and 17.6 days, respectively. At pH 7-8 the stability of purple-blue color and anthocyanin of the extract was extremely low. The half-life of the color and anthocyanin was less than 2 and 10 hours, respectively.